In situ reactor to image catalysts at work in three-dimensions by Bragg coherent X-ray diffraction - Rochet, Amélie; Suzana, Ana Flávia [UNESP]; Passos, Aline R.; Kalile, T.; Berenguer, Felisa; Santilli, Celso V. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Meneau, Florian (Elsevier, 2019)
A new reactor dedicated to high temperature Bragg coherent X-ray diffraction imaging (Bragg CDI) of heterogeneous catalysts at atmospheric pressure has been developed. It allows direct visualisation of the shape, surface texture and inner structures of single nanoparticles with a resolution of a few tens of nanometers. Moreover, in situ Bragg CDI provides information of the displacement field evolution during the reaction. Our setup has been used to observe restructuring in three-dimensions of a model gold catalyst under controlled temperatures and gas atmospheres, He and CO/O2/He. The catalytic performances obtained inside this reactor during the catalytic oxidation of carbon monoxide can be directly correlated with the structural changes of the nanoparticles.
Keywords: Bragg coherent X-ray diffraction imaging; CO oxidation; Gold catalyst; In situ cell